USING 6-3-5 BRAINWRITING IN HELPING SENIOR HIGH SCHOOL STUDENTS DOING BRAINSTORMING IN WRITING PROCESS - Elvi Komala Sari; Fitrawati Fitrawati (Universitas Negeri Padang, 2018)
Abstract This paper discussed about how to apply 6-3-5 Brain Writing in Helping Senior High school Students Doing Brainstorming in Writing Process. 6-3-5 Brain Writing is a group creativity technique in generating new ideas in a short time. It is an alternative method in doing brainstorming. In its traditional format, 6 represent the participants who sit in a group. Each participant should think about 3 ideas in 5 minutes. The ideas are written down in a worksheet that will be provided by the teacher. By using 6-3-5 Brain Writing, the students feel free to write their ideas because critics and comments are not allowed while brainstorming is running. 6-3-5 Brain Writing combines individual work with team. The students write the ideas individually. After the process of brain writing is done, the students evaluate and discuss the ideas in groups. It will help them in generating more ideas in writing as they combine their ideas with others ideas.